The cellular immunity in cancer patients: DNCB test and its prognostic implications - Dighiero, Guillermo; Lassus, Mercedes; Lima, Fabio; Martínez de Lima, Gladys; Priario, Julio C (Cirugía del Uruguay, 1974)
20 normal subjects and 72 neoplasic were testea for their ability to develop delayed cutaneous sensitivity to dinitrochlorobenzene (DNCB). There was a statistical!y significant difference between the reaction of normal subjects· (95 % positives) and neoplasic population ( 50 % ) . Patients who were able to react to DNCB had a significantly better short-term (six and twelve months) prognosis than those who were anergic, and this correlation was also significant in those patients who exhibited advanced neoplasic disease. This study suggests that there might be a significant correlation between the reaction to DNCB and the course of malignant disease.